Brain Tumors and Syndromes in Children - Bleeker, Fonnet E.; Hopman, Saskia M. J.; Merks, Johannes H. M.; Aalfs, Cora M.; Hennekam, Raoul C. M. (Neuropediatrics, 2014)
(Brain) tumors are usually a disorder of aged individuals. If a brain tumor occurs in a child, there is a possible genetic susceptibility for this. Such genetic susceptibilities often show other signs and symptoms. Therefore, every child with a brain tumor should be carefully evaluated for the presence of a “tumor predisposition syndrome.” Here, we provide an overview of the various central nervous system tumors that occur in children with syndromes and of the various syndromes that occur in children with brain tumor. Our aim is to facilitate recognition of syndromes in children with a brain tumor and early diagnosis of brain tumors in children with syndromes. Diagnosing tumor predisposition syndromes in children may have important consequences for prognosis, treatment, and screening for subsequent malignancies and nontumor manifestations. We discuss pitfalls in clinical and molecular diagnoses, and the consequences of diagnosing a hereditary disorder for family members. Our improved knowledge of cancer etiology is increasingly translated into management strategies in syndromes in general and will likely lead in the near future to personalized therapeutic approaches for tumor predisposition syndromes.
Keywords: infant; child; brain tumor; gene; genetic; malformation; syndrome; surveillance